Increased cortical inhibition in depression: a prolonged silent period with transcranial magnetic stimulation (TMS). - Steele, J; Glabus, M; Shajahan, P; Ebmeier, K (2000)
BACKGROUND: Motor slowing in depression may be associated with a relative dopaminergic (DA) deficit. Bradykinesia in Parkinson's syndrome is associated with an abnormally short silent period (SP) using transcranial magnetic stimulation (TMS). We hypothesized that depression would also be associated with a short SP. METHODS: Sixteen patients with DSM-IV depression and 19 matched controls participated. SPs were elicited by exercising the contralateral abductor policis brevis (APB) during TMS. RESULTS: The SP was significantly increased in the patient group. No correlation was found between SP and depression score. CONCLUSION: A long SP suggests increased motor cortical inhibition in depression. This finding is inconsistent with the hypothesis of behavioural motor slowing in depression being associated with Parkinsonian-like mechanisms including the dopaminergic deficit. There is a need for studies incorporating larger patient groups to investigate potential correlations between SP and depression indices.